Seasonal Variation in the Histomorphology and Histochemistry of the Bulbourethral Gland of Gaddi Goat and Gaddi Sheep - Suri, Shalini; Sudhakar, L S; Bhardwaj, R L (Indian Journal of Veterinary Anatomy, 2012)
Twenty four adult animals of each species (Gaddi goat and sheep) were utilized for recording seasonal variation in the histomorphology and histochemistry of bulbourethral glands. Bulbourethral glands were mixed (sero-mucous), tubulo-alveolar, consisting of mostly luminated and a few solid end-pieces, enclosed by a thick fibrous capsule. The gland was predominantly mucous in nature. A few serous end-pieces were also observed scattered either between mucous end-pieces or forming a separate lobule in the center of the gland. The mucous end-pieces were lined by columnar cells with basally placed oval or flat nuclei whereas, serous end- pieces were lined with cuboidal epithelium with rounded nuclei. The diameter of alveoli and tubules (both mucous and serous), solid end-pieces and epithelial height were largest during autumn and lowest during summer season in Gaddi goat and sheep. The secretory blebs and secretions were recorded more during autumn season and these secretions stained intensely for PAS-positive and diastase resistant material and also for cholesterol.